The unexpected George Washington : - Unger, Harlow G. (John Wiley & Sons, 2006)
In this biography of the Father of Our Country, Unger features Washington's role as an involved pater familias within his own household. Striving to portray Washington in humanizing ways, Unger uses his letters to a brood of relations, revealing Washington's precepts of guardianship as well as his ire when his advice on education and comportment was ignored. Deaths frequently required Washington's epistolary attention and commemoration, and from his formal style of expression, Unger coaxes forth Washington's pain and sadness. Alongside life's arc, Unger dwells most on Washington's meticulous operation of the slave-run Mount Vernon and his land speculations in the Ohio River county, scene of Washington's name-making military exploits. Lengthy quotation from Washington's diary and instructions to employees and agents make Unger seem overly enthusiastic about Washington's shopping lists. Yet this focus allows Unger to reveal a Washington who had extravagant tastes, which standard biographies tend to minimize. For history readers interested in private lives. Gilbert Taylor